2014
DOI: 10.1155/2014/975875
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Nursing Students Perceived Knowledge, Attitudes, and Practices concerning Human Immunodeficiency Virus

Abstract: Objective. To assess medical and nursing students' knowledge, attitudes, and practices (KAP) regarding human immunodeficiency virus (HIV) in Fiji. Methods. A cross-sectional study of 275 medical and 252 nursing students that participated in a questionnaire survey on HIV KAP. Data was analysed according to their gender, program of study, and academic year. Results. The mean HIV knowledge (HK) and attitude scores were 16.0 and 41.3, respectively. Mean HK score was significantly higher in males compared to female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 18 publications
5
15
0
1
Order By: Relevance
“…The demographic details of the students such as age, sex, parent's occupation, family income, and source of information about HIV/AIDS were recorded. The attitude level of the students was assessed by using structured AIDS attitude assessment scale (AAAS) [13,14]. It consisted of 15 questions from the HIV knowledge attitude perception (KAP) questionnaire formulated by Magazine and Silas et al [13,14], which were selected and modified according to the sensitivity of the student group and cultural value.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic details of the students such as age, sex, parent's occupation, family income, and source of information about HIV/AIDS were recorded. The attitude level of the students was assessed by using structured AIDS attitude assessment scale (AAAS) [13,14]. It consisted of 15 questions from the HIV knowledge attitude perception (KAP) questionnaire formulated by Magazine and Silas et al [13,14], which were selected and modified according to the sensitivity of the student group and cultural value.…”
Section: Methodsmentioning
confidence: 99%
“…The attitude level of the students was assessed by using structured AIDS attitude assessment scale (AAAS) [13,14]. It consisted of 15 questions from the HIV knowledge attitude perception (KAP) questionnaire formulated by Magazine and Silas et al [13,14], which were selected and modified according to the sensitivity of the student group and cultural value. Reliability of tool was tested by test-retest method, as r = 0.7, and content validity was obtained from the experts.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] It is very important that nurses be educationally prepared to give safe, skilled and systematic care for patients irrespective of their diagnosis. [15] Knowledge of AIDS, especially knowledge on the mode of transmission to relieve the fear of caring for PLHIV, [20] will lead to improvement in the care.…”
Section: Introductionmentioning
confidence: 99%
“…14 Our study reveals that the fear of contagion of the students that do not consider their knowledge on HIV/AIDS sufficient is higher than those that do (p=0.010) ( Table 5). This might be related to a fear of the unknown resulting from not having enough information about HIV/AIDS or thinking that the protective precautions against contagion in clinics are not adequate.…”
Section: Discussionmentioning
confidence: 63%
“…Studies have shown that enhancing the knowledge about HIV/AIDS significantly increases attitude points in a positive way and that fear of contagion can be reduced through education. 11,12,[14][15][16][17] When the findings related to the sub dimensions of AIDS Attitude Scale in terms of gender are looked at (Table 4), it can be seen that female students have a more positive attitude towards HIV/AIDS patients than male students regarding negative feelings and professional resistance subdimensions. Female students have also significantly higher empathic tendency than male students.…”
Section: Discussionmentioning
confidence: 99%